THE EFFECTIVENESS OF THE USE OF TIME TOKEN LEARNING METHOD ON ENGLISH COMMUNICATION SKILLS OF AMIR HAMZAH UNIVERSITY STUDENTS MEDAN - Tambusai, Azhary; Muhammad Khalid; Khairina Nasution (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
English is an international language that is taught at all levels of education. In Amir Hamzah University itself, English learning is needed to improve learning outcomes and student motivation. One of the learning methods to improve English proficiency for Amir Hamzah students is the time token method. This learning method is one of the methods that provides opportunities for students to be able to express their opinions in English actively. So that the negative effects of learning dependence can be avoided. The existence of the time token learning method encourages students to increase initiative and participation, avoiding the dominance of students who are good at speaking or who do not speak at all, helping students to be active in learning activities.